2023
DOI: 10.1007/s10814-023-09191-1
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture in the Ancient World: Ecosystem Engineering, Domesticated Landscapes, and the First Blue Revolution

Ashleigh J. Rogers

Abstract: Aquaculture is the world’s fastest growing food sector and accounts for more than 50% of the world’s fish food supply. The significant growth in global aquaculture since the middle of the 20th century has been dubbed by the Blue Revolution. However, it is not the first Blue Revolution to take place in human history. While historically classified as low-ranking, seasonal, or starvation resources in the archaeological discourse, marine foods were vital resources that ancient communities developed and exploited u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 221 publications
0
7
0
1
Order By: Relevance
“…Bird et al, 2016; Bliege Bird et al, 2018; Crabtree et al, 2019; Levis et al, 2017) or millennia-long food production systems survive enormous environmental and climatic shifts only to collapse after European arrival (e.g. Reeder-Myers et al, 2022; Rogers, 2023; Thompson et al, 2020). Understanding ecosystem functioning prior to the transformative effects of people, particularly European colonisers, is essential for present-day food security challenges, with the goal of restoring environmental integrity and alleviating biodiversity crises (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bird et al, 2016; Bliege Bird et al, 2018; Crabtree et al, 2019; Levis et al, 2017) or millennia-long food production systems survive enormous environmental and climatic shifts only to collapse after European arrival (e.g. Reeder-Myers et al, 2022; Rogers, 2023; Thompson et al, 2020). Understanding ecosystem functioning prior to the transformative effects of people, particularly European colonisers, is essential for present-day food security challenges, with the goal of restoring environmental integrity and alleviating biodiversity crises (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…What is rarely reported, however, is the impact terrestrial and indeed littoral alterations (e.g. fishpond and trap construction : Fitzpatrick, 2020;Rogers, 2023), may have had on marine ecosystems. An exception is recent work by Fitzpatrick and Giovas (2021), who reconstructed feedback loops between terrestrial food producing systems and marine environments in Palau, Micronesia, and the Lesser Antilles, Caribbean, documenting long-term sustainable and responsive decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Equally as agricultural food production, aquaculture fish farming is also having a key role in food security, because this type of food production is capable to reduce food shortages and avoid the exploitation of the international fish markets [99]. The last years have shown that the consumption of food elaborated in aquaculture has incremented [20], but this increased demand for elaborated products based on aquatic animal production and the advanced use of production spaces have created a critical ecological impact [100].…”
Section: Groundwater Usage and The Environmental Impact In Aquacultur...mentioning
confidence: 99%
“…Aquaculture is another water intensive sector of food production which is contributing to food security [18] requiring great freshwater inputs for the production process of aquatic animals [19]. Terrestrial aquaculture is considered part of the blue revolution due to the domestication of the aquatic landscape to generate more food inside a functional ecosystem, but todays aquacultural production is exercised in intensive monoculture causing pollution due to the emission of waste materials, aquatic feed contamination and nutrient discharges [20]. Moreover, aquaculture food production is an increasing industrial sector, which requires even more access and use of groundwater resources [21].…”
Section: Introductionmentioning
confidence: 99%
“…И рядом с мидденами или даже на их поверхности возникали поселения, жители которых естественным образом развивали приморскую экономику, занимаясь сбором водорослей, рыбной ловлей и добычей морского зверя, что также отразилось в составе кухонных отходов. Наблюдения за характеристиками раковин навело на мысль, что в некоторых местах население переходило от простого собирательства к выращиванию моллюсков определенного вида и размера, в результате чего сложилась аквакультура как особый тип производящего хозяйства [Раков, Бродянский, 2007;Rogers, 2023]. Впрочем, подобные изменения в составе раковин в кучах могли быть результатом специализированного промысла в рамках приморской адаптации в целом [Табарев, 2007].…”
Section: ценные отбросыunclassified